2009
DOI: 10.1007/s11258-009-9573-8
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathy as a mechanism for the invasion of Typha angustifolia

Abstract: The direct competitive effects of exotic plants on natives are among the leading causes of plant extinctions worldwide. Allelopathy, one type of direct plant competition, has received relatively little research, particularly in aquatic and wetland systems, even though allelopathy can be a potent mechanism through which plant communities are structured. Typha angustifolia (narrow-leaved cattail) is an invasive exotic plant in North America that often forms monocultures in disturbed wetlands and is more invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…The most likely explanation is that allelochemicals released by the invasive species were degraded by the soil microbial community (Barto & Cipollini 2009;Kaur et al, 2009;Zackrisson & Nilsson 1992), and thus could not affect native species in the long term. Our finding fits into a growing body of evidence which shows that invasive species release allelochemicals that immediately affect their competitors (Abhilasha et al, 2008;Gomez-Aparicio & Canham 2008;Jarchow & Cook 2009;Murrell et al, 2011;Newingham & Callaway 2006;Ridenour & Callaway 2001). Due to the high number of invasive species studied, we can conclude that immediate allelopathy of invasive species generally decreases the competitive ability of natives.…”
Section: Immediately Effective Biochemicals Affect Plants Negativelysupporting
confidence: 86%
“…The most likely explanation is that allelochemicals released by the invasive species were degraded by the soil microbial community (Barto & Cipollini 2009;Kaur et al, 2009;Zackrisson & Nilsson 1992), and thus could not affect native species in the long term. Our finding fits into a growing body of evidence which shows that invasive species release allelochemicals that immediately affect their competitors (Abhilasha et al, 2008;Gomez-Aparicio & Canham 2008;Jarchow & Cook 2009;Murrell et al, 2011;Newingham & Callaway 2006;Ridenour & Callaway 2001). Due to the high number of invasive species studied, we can conclude that immediate allelopathy of invasive species generally decreases the competitive ability of natives.…”
Section: Immediately Effective Biochemicals Affect Plants Negativelysupporting
confidence: 86%
“…While allelopathic effects of introduced invasive species on native resident species have received much attention (e.g. Hierro and Callaway 2003;Orr et al 2005;He et al 2009;Jarchow and Cook 2009;Del Fabbro et al 2014), the reverse the allelopathic effect of a native community on introduced species has been largely neglected (Cummings et al 2012;Hou et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been suggested that many highly invasive introduced plant species can dominate plant communities because they produce allelopathic compounds that are novel to the native resident plants (Callaway and Ridenour 2004). Because of this novelty, and a lack of co-evolutionary history with the introduced invasive species (Verhoeven et al 2009;Saul et al 2013), the native species may be strongly affected by the allelopathic chemicals (Callaway and Vivanco 2007;Jarchow and Cook 2009;Gruntman et al 2014). Indeed, there are many studies showing that the competitive ability of invasive introduced plants is partly mediated by allelopathy (Ens et al 2009;Murrell et al 2011;Bauer et al 2012;Svensson et al 2013;Del Fabbro et al 2014), and thus might contribute to invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathic effect of some invasive species is stronger on other species in introduced ranges than in native ranges because in new habitat species may not be as adapted to specific allelochemicals of invaders as species do in the native range [10]. Most of invasive plant species has competitive and defensive characteristics which accounts to allelopathic impact [3] [10] [14]. Allelochemicals also affect native species through different pathways that includes interruption of plants nutrients uptake, change in membrane permeability [15], interference in cell division and elongation in roots and shoots [16]- [18], interference in chlorophyll formation [19], protein synthesis inhibition [15] [20] and change or inactivate the activity and functions of certain hormones and enzymes [15] [21].…”
Section: Introductionmentioning
confidence: 99%